Educational Values in the Novel Trilogy â€œSepatu Dahlan, Surat Dahlan, dan Senyum Dahlanâ€ by Khrisna Pabichara (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study is to analyze the educational values contained in the novel â€œSepatu Dahlan, Surat Dahlan, dan Senyum Dahlanâ€ by Khrisna Pabichara. This research uses structuralism approach. This research data is fragments of text, sentences, and dialogue contained in the novel trilogy works of Khrisna Pabichara allegedly the element of the builder of literary works and educational values. Data collection is done by a non-interactive method, which is to study documents and archives. The technique of collecting data from this research is a technique of referring, record, and literature study. The results of this research data analysis are presented using content analysis data or content analysis in the form of structure and educational values in the novel trilogy by Khrisna Pabichara. The findings of this study on the educational values contained in the novel â€œSepatu Dahlan, Surat Dahlan, dan Senyum Dahlanâ€ by Khrisna Pabichara's are exemplary.